CysLT sub(1)-R expression following allergen provocation in asthma and allergic rhinitis - Boulay, Marie-Eve; Duchesneau, Edith; Jacques, Eric; Chakir, Jamila; Boulet, Louis-Philippe (Prostaglandins, leukotrienes and essential fatty acids, 2010)
Cysteinyl leukotrienes (CysLTs) contribute to allergic and inflammatory diseases through CysLT sub(1)-R. We aimed to assess CysLT sub(1)-R mRNA expression in induced sputum of rhinitics with or without asthma before and following allergen challenges. Both groups underwent nasal and "low dose" lung allergen challenges. Asthmatics also underwent "standard" lung challenge. Sputum was obtained before and at different time-points following the challenges for CysLT sub(1)-R, 5-lipoxygenase (5-LO), and eotaxin mRNA assessments. At baseline, there was no difference in mediator levels between groups. An increase in CysLT sub(1)-R mRNA (p=0.04) and a trend towards an increase in 5-LO and eotaxin (p=0.06 for both) at 24 h post-nasal challenge were observed. Following "low dose" lung allergen challenge, there was a trend towards an increase in CysLT sub(1)-R (p=0.07). In conclusion, CysLT sub(1)-R gene expression changes can be detected in sputum following allergen challenges. No difference was observed between groups, suggesting that changes in CysLT sub(1)-R expression occur whether or not the subject has concurrent asthma.